Où sommes-nous quand nous sommes à l’école ? - Philippe Foray (Recherches en Éducation)
Where are we when we are in school? The answer of the political french tradition to this question connects the school with the public realm. School is a public institution. Thought of Hannah Arendt (and Paul Ricoeur) suggests another answer: school doesn’t belong only to one domain; she stands at the intersection of several (private, social, public). This article expounds this idea. Then, it examines some of consequences about the bind between school and secularization